Prostaglandin E2 Inhibit Cyclooxygenase-2 Induction In lps-treated Endothelial Cells Through Camp - Akarasereenont, Pravit; Techatrisak, Kitirat; Thaworn, Athiwat; Chotewuttakorn, Sirikul (Journal of Basic and Applied Pharmacology, 2015)
Cyclooxygenase (COX), which exists as COX-1 and COX-2 isoforms, is the first enzyme in the pathway in which arachidonic acid is converted to prostaglandins (PGs). PGE2 is one of the PGs which have numerous cardiovascular and inflammatory effects. PGE2 also exerts a variety of biological activities for the maintenance of local homeostasis in the body. Elucidation of PGE2 involvement in the signalling molecules such as COX could lead to potential therapeutic interventions. Here, we have investigated the effects of PGE2 on the induction of COX-2 in human umbilical vein endothelial cells (HUVEC) treated with lipopolysaccharide (LPS; 1 μg/ml). COX activity was measured by the production of 6-keto-PGF1α, PGE2, PGF2α and TXB2 in the presence of exogenous arachidonic acids (10 μM for 10 min) using enzyme immunoassay (EIA). COX-1 and COX-2 protein was measured by immunoblotting using specific antibody. Untreated HUVEC contained only COX-1 protein while LPS treated HUVEC contained COX-1 and COX-2 protein. PGE2 (3 μM for 24 h) did not affect on COX activity and protein in untreated HUVEC. Interestingly, PGE2 (0.003, 0.03 and 3 μM for 24h) can inhibit COX-2 protein, but not COX-1 protein, expressed in HUVEC treated with LPS (1 μg/ml) in a dose dependent manner. Moreover, this inhibition was reversed by coincubation with foskolin ( cAMP activator; 100 μM). The increased COX activity in HUVEC treated with LPS was also inhibited by PGE2 (0.03, 0.3 and 3 μM for 24h) in a dose dependent manner. Similarly, foskolin (10, 50 or 100 mM) can also reverse the inhibition of PGE2 on increased COX activity in LPS treated HUVEC. The results suggested that i) PGE2 can be negative feedback regulation in the induction of COX-2 elicited by LPS in endothelial cells, ii) the inhibition of PGE2 on COX-2 protein and activity in LPS treated HUVEC was mediated through cAMP and iii) the therapeutic uses of PGE2 in the pathological conditions which COX-2 has been involved may have roles.